2019
DOI: 10.1111/jcmm.14521
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of a KCNH2 mutant: Novel insights on the pathogenesis of the LQT2 syndrome

Abstract: The K+ voltage‐gated channel subfamily H member 2 (KCNH2) transports the rapid component of the cardiac delayed rectifying K+ current. The aim of this study was to characterize the biophysical properties of a C‐terminus‐truncated KCNH2 channel, G1006fs/49 causing long QT syndrome type II in heterozygous members of an Italian family. Mutant carriers underwent clinical workup, including 12‐lead electrocardiogram, transthoracic echocardiography and 24‐hour ECG recording. Electrophysiological experiments compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Recognizing the genetic substrate underlying the inherited arrhythmia syndromes has remarkably improved the field of the molecular basis of cardiac electrophysiology, including arrhythmia mechanism and the role of the different ion channels [ 2 , 3 ]. Genotype-phenotype study relationships, performed mainly for the LQTS, have uncovered the importance of genetic aspects of disease and proved that the patient's management should consider the nature of the gene affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the genetic substrate underlying the inherited arrhythmia syndromes has remarkably improved the field of the molecular basis of cardiac electrophysiology, including arrhythmia mechanism and the role of the different ion channels [ 2 , 3 ]. Genotype-phenotype study relationships, performed mainly for the LQTS, have uncovered the importance of genetic aspects of disease and proved that the patient's management should consider the nature of the gene affected.…”
Section: Discussionmentioning
confidence: 99%
“…These genetic disorders include the LQTS, SQTS, catecholaminergic polymorphic ventricular tachycardia, idiopathic atrial fibrillation, and Brugada syndrome. One of these channels is the potassium channels that are the primary contributors to the repolarization process, which appeared to underlie LQTS in case of dysfunction especially when mutations in genes encoding for pore-forming α -subunits (KCNQ1, KCNH2) of these channels are detected [ 2 , 3 ]. KCNH2 (potassium voltage-gated channel subfamily H member 2), one of many genes, reported having a refractory fever-induced TdP and VF in two related LQT2 patients with the A558P mutation in KCNH2.…”
Section: Discussionmentioning
confidence: 99%
“…Nav1.5 GFP-tagged and β 1 subunit constructs were kindly provided by Paola Imbrici from Department of Pharmacy-Drug Sciences, University of Bari, Italy. GFP-tagged KCNH2 encoding plasmid was previously characterized by us ( De Zio et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiology on KCNH2-expressing HEK293 cells was conducted as previously described ( De Zio et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…KCNH2 is expressed in many tissues, including the heart and the brain. Previous evidence has demonstrated that KCNH2 plays an important role in the repolarization of the heart [9]. Recent ndings have also revealed that KCNH2 is also overexpressed in ductal, lobular, and invasive breast carcinomas [10].…”
Section: Introductionmentioning
confidence: 97%